2015
DOI: 10.18632/oncotarget.3321
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-R2 promotes skeletal metastasis in a breast cancer xenograft mouse model

Abstract: Despite improvements in detection, surgical approaches and systemic therapies, breast cancer remains typically incurable once distant metastases occur. High expression of TRAIL-R2 was found to be associated with poor prognostic parameters in breast cancer patients, suggesting an oncogenic function of this receptor. In the present study, we aimed to determine the impact of TRAIL-R2 on breast cancer metastasis. Using an osteotropic variant of MDA-MB-231 breast cancer cells, we examine the effects of TRAIL-R2 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…RNAi-based approaches have been used as therapeutic methods for the treatment of a variety of tumor types 64 65 . In the present study, we injected CHOP-siRNA directly into the abdominal cavities of nude mice burdened by ESCC cell xenografts and found that, at day 20 after the first injection, the mean tumor volume of the tested group was increased by 38.63% compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi-based approaches have been used as therapeutic methods for the treatment of a variety of tumor types 64 65 . In the present study, we injected CHOP-siRNA directly into the abdominal cavities of nude mice burdened by ESCC cell xenografts and found that, at day 20 after the first injection, the mean tumor volume of the tested group was increased by 38.63% compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…There is furthermore evidence that TRAILinduced cell migration in KRAS-mutated cells is of the mesenchymal type and thus dependent on mutant KRAS-mediated suppression of ROCK activity which drives otherwise, as discussed above, an amoeboid form of cell migration that can also be induced by death receptors. Proliferation, activation of Akt and Src as well as enhanced bone metastasis along with epithelial mesenchymal transition have furthermore been demonstrated in response to TRAILR2 activation in a xenograft model with a highly osteotropic clone of the MDA-MB-231 breast cancer cell line [157]. Noteworthy, in this model, the ability of TRAILR2 to interact with FADD was found to be dispensable for promotion of metastasis, too, but otherwise the molecular basis of the protumoral activity of TRAILR2 has not been evaluated in this study.…”
Section: Cell Migration and Invasion Can Be Induced By Several Cd95-amentioning
confidence: 97%
“…While there are now patient‐derived tumor xenograft models to study BC growth and metastasis using either human (Rowan et al, ; Dahibawkar et al, ; Fritsche et al, ; Sp et al, ) or mouse‐derived cancer cell lines (Singh et al, ; Zou et al, ), there is no mouse model for studying normal breast tissue biology such as that required for examining high MD‐associated BC risk. The complex cellular interactions that underpin MD and BC cannot be easily created in an in vitro setting, thus our pilot study demonstrated the value of our murine biochamber as a model to assess altered cellular function in HMD and LMD human mammary tissues.…”
Section: Discussionmentioning
confidence: 99%